(untitled) (RIVISTA ITALIANA DI PALEONTOLOGIA E STRATIGRAFIA, 2014)
The Slovenian Basin was a Mesozoic deep-water paleogeographic domain located north of the Dinaric Carbonate Platform. Due to a considerable amount of southward-directed thrusting and subsequent erosion, the marginal parts of this basin are only sparsely preserved. The southernmost remains of the Slovenian Basin in western Slovenia are found in the Ponikve Klippe, where we studied a Middle Jurassic (? Aalenian) to Lower Cretaceous (Albian) succession. We dated the succession with radiolarians, calpionellids, and benthic foraminifers. The succession is divided into three formations. The first is the Middle Jurassic to Lower Tithonian Tolmin Formation, composed of radiolarian cherts, siliceous limestone, and calciturbidites. The second formation is the Upper Tithonian–Berriasian Biancone limestone, which consists of pelagic limestone with calpionellids and one interstratified calciturbidite. The third formation, the Lower flyschoid formation, rests upon a prominent, regionally recognized erosional unconformity. The formation begins with calcareous breccia and continues with finer-grained calciturbidites that alternate with marl/shale and chert. Only the lower part of this formation was investigated and dated to the late Aptian to early Albian. The correlation of the studied section with the previously described successions of the Slovenian Basin shows that the Jurassic part of the section clearly exhibits a more marginal setting, whereas the Cretaceous part of the section correlates well with the central basinal succession. This inversion was related to the late Aptian tectonic event that was also responsible for the considerable submarine erosion and deposition of the basal breccia of the Lower flyschoid formation.